Distribuição geográfica e evolução das notificações de leishmaniose tegumentar americana pelo sistema de informação de agravos de notificação (SINAN) no Estado do Paraná - Alcântara, Léia Regina de Souza (2016)
Leishmaniasis is infectious diseases caused by protozoa of the genus Leishmania. They are widely distributed throughout the world, endemic in 98 countries on four continents. This study showed the outcome of leishmaniasis notifications (ACL) in the state of Paraná and the predictors associated with the ACL in a Regional Health (RH) of the North of Paraná state region. The study was characterized as descriptive and cross, in which epidemiological data ACL obtained from the tabulation of the data available at the DATASUS database (Department of Health System Hardware) of Brazil. Notified cases of ACL were distributed among the 22 RH and showed average detection rate of 3.9 cases / 100,000 inhabitants. The Northwest reported 50.1% of cases and the North 26.0% to 76.1% of the notifications. The 6th RH showed no information. The 7th, 9th and 18th RH had a higher cure rate, above 80% and the lowest cure rates observed in the 1st (28.5%), 4th (33.3%) and 12th RH (46.3%). Unfavorable outcomes were leaving (2.1%) and death (0.4%) unfavorable results may be related to adverse effects of treatment. Although the cure rate is consonant to the whole national territory, adverse outcomes require more attention from managers and health professionals to fulfill the Ministry of Health's goal. To determine the association between risk factors and the ACL 18th in the state of Paraná RH was used to measure Odds ratio (OR) and applied the chi-square or Fisher's exact test using a significant p-value when <0.05. Later reported cases were spatial distribution by preparing maps using Geographic Information System (GIS) Spring, version 5.3. All reported cases were the cutaneous form. The city of Bandeirantes presented a risk to the CL of nearly nine times more than the other OR = 8.56. The prevalence of CL in the countryside (10.90 cases per 10,000 inhabitants) was 2.44 times greater (OR = 2.44). Concerning gender highlights the city of Bandeirantes, where the likelihood of women acquiring CL (50 cases) was almost twice as compared to men (28 cases; OR = 1.79). The most affected age group was more than 20 years (OR = 6.39. Individuals who declared themselves illiterate, even those who had not completed elementary school, had a chance four times more likely to have CL (OR = 4.12), compared to those who have completed elementary school or more. The cases spatial showed the prevalence, where the use of land is for intensive agriculture, soils with higher water Retention capacity, at altitudes between 400 m and 850 m. The cases of CL belonged to watersheds Paranapanema and Tibagi.